Recent development in surface modification of industrial materials by ion beams and plasma at Chiang Mai University - L. D. Yu (2018)
Recently, programs of surface modification of materials for local industries by ion beams and plasma have been vigorously carried out and related facilities, technologies and applications have been continuously developed at Chiang Mai University on the basis of previous work. Some examples are presented. Punching tools from local industry were N-ion implanted with a specially designed process to achieve both high hardness and impact toughness so as to increase the lifetime of the tools by 3-4 times. High-fluence N-ion implantation in stainless steel of the fuel cell plates increased corrosion resistance. Plasma immersion ion implantation and deposition (PIII/D) coated diamond-like carbon (DLC) thin films on various substrate materials such as stainless steel of the fuel cell plates, glass of the plastic lens mould, and magnets of the dental rectification accessories to improve both mechanical and chemical properties. Plasma treatment of commercial textiles modified the wettability of the material. The development in the ion beam and plasma applications for industries has promoted research for understanding physics involved as well as student education of the university. © 2009 Elsevier B.V. All rights reserved.